Effects of perceived overqualification on career distress and career planning: Mediating role of career identity and moderating role of leader humility - Ma, Chao; Ganegoda, Deshani B.; Chen, (George) Zhen Xiong; Jiang, Xinhui; Dong, Chunyan (Human Resource Management, 2020)
AbstractIn this study, we examined how perceived overqualification influences employees' career distress and career planning. Specifically, we drew on role identity theory to hypothesize that perceived overqualification is positively related to individuals' career identity. Based on internal self‐processing dynamics of role identity, we further hypothesized that career identity predicts reduced career distress and increased career planning. We expected career identity to mediate the effects of overqualification on career distress and career planning. Based on the symbolic interactionism perspective of identity, we hypothesized that this mediation is moderated by leader humility so that overqualified employees exhibit stronger career identities in the presence of a humble leader. We found support for our hypotheses in a multi‐wave time‐lagged study of 220 supervisor–subordinate dyads from 50 groups. Overall, our studies highlight that perceived overqualification can have positive effects on employees and organizations under appropriate management conditions. We discuss theoretical and practical implications of these results.